SOCIAL MEDIA HIGHLIGHTS : A PUBLIC SENTIMENT ANALYSIS OF THE SPEECHES OF THE MINISTER OF YOUTH AND THE PRESIDENT OF INDONESIA - Zahroh, Muchlishatuz; Adianto Budiman, Ramadan (Universitas Sebelas Maret, 2024)
The 2018 Asian Games was a prestigious sporting event that attracted public attention. The speeches of the Minister of Youth and Sports (Menpora) and the President of Indonesia at the event became an important moment that triggered public discussion and reaction. This research aims to analyze public sentiment towards both speeches through social media, especially Twitter. Previous research on public sentiment towards the Asian Games generally focused on aspects of organization, athletes, and achievements. This research focuses on analyzing the sentiment towards the speeches of national leaders, which provides a new perspective on how the public responds to the messages and narratives delivered. This research uses sentiment analysis method with lexicon-based approach. Data was collected from Twitter using keywords related to the speeches of the Menpora and the President of the Republic of Indonesia. The data was then processed using sentiment analysis software to classify the sentiment into positive, negative, and neutral. The results of the analysis show that public sentiment towards the speeches of the Minister of Youth and Sports and the President of the Republic of Indonesia tends to be positive. There are a number of dominant topics in public discussions, such as the spirit of nationalism, support for athletes, and hope for achievement. This research shows that social media is an important platform for understanding public sentiment towards national issues, such as the Asian Games. The speeches of the Minister of Youth and Sports and the President of Indonesia succeeded in generating enthusiasm and positive spirit among the public. The results of this study can be taken into consideration for the government in formulating future public communication strategies.